Dietary advanced glycation end products modify gut microbial composition and partially increase colon permeability in rats. Issue 10 (31st July 2017) - Qu, Wanting; Yuan, Xiaojin; Zhao, Jinsong; Zhang, Yingxiao; Hu, Jing; Wang, Jiawei; Li, Juxiu
Abstract : Scope: The adverse impacts of dietary advanced glycation end products (AGEs) on health are currently of interest. These compounds are inevitably formed during thermal food processing and make foods less digestible because of protein cross‐linking. This study examined not only whether dietary AGEs alter cecal microbiota and their metabolites but also their effects on colon permeability. Methods and results: Sprague–Dawley rats were exposed to a high‐AGEs diet (AGEs content was increased by heating food at 125°C/3 h) for 6, 12, or 18 weeks. Cecal microbiota was analyzed by 16S rDNA gene sequencing. Colon permeability was assessed through histopathology, immunohistochemistry and endotoxin testing. Microbial metabolites (e.g. ammonia and short‐chain fatty acids (SCFAs)) were also measured. AGEs treatment reduced the diversity and richness of the microbiota, especially saccharolytic bacteria such as Ruminococcaceae and Alloprevotella, which can produce SCFAs, whereas some putatively harmful bacteria ( Desulfovibrio and Bacteroides ) were increased. Protein fermentation was enhanced, supported by elevated ammonia and branched‐chain fatty acid levels ( p  < 0.05). Additionally, the colonocytes structure changed and the expression of tight junction proteins in colon were decreased. Conclusion: Dietary AGEs detrimentally modulate gut microbial ecology and may partially increase colon permeability, which can adversely impact host health. Abstract : Rats were exposed to a high‐AGEs diet, in which AGEs content was elevated by heating the food at 125°C/3 h, for 6, 12, or 18 weeks. The effects of dietary AGEs on cecal microbiota composition, metabolites of ammonia and SCFAs concentrations, and colon barrier function were examined. α‐diversity and richness of the microbiota reduced and community structure changed after dietary AGEs treatment. Protein fermentation was enhanced in colon. Dietary AGEs also altered colonocytes structure, decreased the expression of tight junction proteins in colon, showing it partially increase colon permeability.